2008
DOI: 10.1007/s00467-008-0871-5
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of chronic kidney disease (stages 2–5) in KwaZulu-Natal, South Africa

Abstract: The burden of chronic kidney disease (CKD) in children in developing countries remains unknown, due to the lack of a national data-reporting system. We undertook a retrospective study of all children < 16 years old in our hospital, which is the tertiary referral centre for children with complex kidney disorders, to analyse the spectrum of CKD (stages 2-5) from 1994-2006. Six hundred and fifty-three children with kidney disorders were screened for CKD; 286 (44.0%) were < 5 years old. Of these, 177 (62%) were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
6
26
2
Order By: Relevance
“…To the best of our knowledge none of the studies were reported exclusively on children in ESRD and therefore, our study adds important new information to the epidemiology of ESRD among Nigerian children. Our study showed that the incidence of paediatric ESRD was higher than previously reported from our sub region [1,2,13] but lower than those reported in developed countries [8,9,11,23]. Glomerulonephritis was the commonest cause, followed by CAKUT.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…To the best of our knowledge none of the studies were reported exclusively on children in ESRD and therefore, our study adds important new information to the epidemiology of ESRD among Nigerian children. Our study showed that the incidence of paediatric ESRD was higher than previously reported from our sub region [1,2,13] but lower than those reported in developed countries [8,9,11,23]. Glomerulonephritis was the commonest cause, followed by CAKUT.…”
Section: Discussioncontrasting
confidence: 56%
“…There are few studies on childhood ESRD from sub-Saharan Africa [1,2,12,13]. To the best of our knowledge none of the studies were reported exclusively on children in ESRD and therefore, our study adds important new information to the epidemiology of ESRD among Nigerian children.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Single-center studies from sub-Saharan Africa have shown a very low incidence of CKD, estimated at 3 pmarp in Nigeria, which did not offer pediatric RRT, and 1–2 pmarp in South Africa [23, 24]. …”
Section: Demographics Of Ckdmentioning
confidence: 99%
“…Nephrotic syndrome was also observed as the most common etiology of CKD in KwaZulu-Natal, South Africa, with 30.9% in children aged < 5 years and 40.8% in children > 5 years. 12 The prevalence of ESRD at presentation in our study was 21.8%. This number is much lower than that found in the studies in Turkey (32.5%) 4 and Sudan (63%).…”
Section: Resultsmentioning
confidence: 42%